Identifying of a bird figure of the Nazca pampas of southern coast of Peru: a discussion post - Karl , Hans-Volker; safi, Amtyaz; Tichy , Gottfried (International Journal of Biological Research, 2023)
Nazca is a city and system of valleys on the southern coast of Peru. The name is derived from the Nazca culture, which flourished in the area between 100 BC and 800 AD. Nazca Lines contain over 800 straight lines, 300 geometric figures and 70 biomorphic designs. Some of the straight lines are 30 miles long, while the largest bio morphs stretch up to 1200 feet. Among the zoomorphic figures are the famous Nazca condor, hummingbird, pelican, shark, bird, fish, spider, lizard, parrot, flamingo, iguana, dog, llamas, jaguar, fox, whale and monkey. We have identified a studied figure of Nazca Pampas as a species of umbrella birds (Cephalopterus) and this geoglyph has more resemblances with the short-lobed parasol (Cephalopterus ornatus) than any other species.